Digital Cultures and the Politics of Emotion - Karatzogianni, Athina. author. aut Link
XIII, 272 p.
Keywords: Fifteen thought-provoking essays engage in an innovative dialogue between cultural studies of affect, feelings and emotions, and digital cultures, new media and technology. The volume provides a fascinating dialogue that cuts across disciplines, media platforms and geographic and linguistic boundaries.